JUVENILE CHRONIC MYELOID LEUKEMIA - Mannan, Modoodul; Khaliq, M.A. (Journal of Ayub Medical College Abbottabad, 1991)
Two cases of Juvenile Chronic Myeloid Leukemia (CML) are reported. The commonest age of CML is fourth and fifth decades of life, the disease is rare in children specially below the age of ten years. We have found two cases of Juvenile CML, one aged 1 year and other 8 years old. These cases were referred to us from Women and Children Hospital, Abbottabad